Electrochemical Studies of Transition Metal Complexes (International Journal of Engineering & Extended Technologies Research (IJEETR), 2021)
Electrochemical investigations of transition metal complexes provide critical insights into redox behavior, ligand influence, and application potential in catalysis, sensing, and electrochromic devices. Before 2020, cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and spectroelectrochemical techniques enabled characterization of metal-centered and ligand-based electron-transfer processes across a wide range of systems. For example, benzimidazole-based complexes of Fe(II), Cu(II), Co(II), and Mn(II) demonstrated clear multielectrochromic behavior, with Fe(II) complexes stably cycling through multiple redox states and color changes, making them promising for electrochromic devices .Terpyridine-based metal complexes revealed how substituent electronic effects (electron-donating vs. electronwithdrawing groups) significantly alter redox potentials and reversibility, emphasizing ligand control over electrochemical profiles . Comparative CV studies of Co²⁺, Ni²⁺, Cu²⁺, Zn²⁺, and Cd²⁺ complexes with thiazole-derived Schiff base ligands further underscored that ligand scaffolds modulate reduction/oxidation peak positions and current intensities, highlighting structure–property relationships . Palladium–phenanthroline complexes displayed high electrochemical stability through consistent redox peaks across multiple CV cycles, pointing to potential use in catalysis and energy storage .Additionally, electrochemical impedance and cyclic voltammetric studies of Ni(II) and Co(II) coordination polymers prepared via solvothermal methods showed tailored electrode behavior, with morphology–structure correlations affecting charge-transfer resistance and voltammetric responses .Together, these studies—spanning mononuclear organometallic species, coordination polymers, and varied ligand systems—demonstrate that electrochemistry is a sensitive probe for elucidating redox mechanisms, gauging stability, and guiding design in functional materials. This paper synthesizes the methodologies, findings, advantages, limitations, and trajectories emerging from 2020 electrochemical exploration of transition metal complexes.
Keywords: Transition Metal Complexes; Cyclic Voltammetry (CV); Electrochemical Impedance Spectroscopy (EIS); Electrochromism; Ligand Effects; Coordination Polymers; Redox Stability; Structure–Property Relationships; Electrocatalysis; Energy Storage